Accuracy of preoperative T and N staging in colon cancer – a national population‐based study. (January 2016) - Sjövall, A.; Blomqvist, L.; Egenvall, M.; Johansson, H.; Martling, A.
Abstract: Aim: To select patients for neoadjuvant therapy in colon cancer, there is a need to improve pre‐therapeutic locoregional staging. There are now data showing that the TN stage can be adequately assessed by preoperative CT in dedicated centres. In Sweden the use of preoperative CT of the abdomen for staging of the primary tumour is increasing. The aim of this study was to determine to what extent the preoperatively reported radiological TN stage correlates with the histopathological TN stage in an entire population. Method: Data were collected on the preoperative cTN stage according to the radiologist and postoperative pTN stage according to the pathologist on all patients operated on for colon cancer in Sweden 2007–2010. The correlation between cTN stage and pTN stage was calculated using kappa statistics. Results: T stage was compared in 4373 patients with cT and pT stage. The correlation coefficient was 0.44, indicating fair agreement. The cN and pN correlation coefficient was 0.28, indicating a slight correlation. There was no difference in correlation related to age, gender, tumour location, body mass index or emergent vs elective surgery. A slight difference was seen between different geographical regions. Conclusion: Preoperative CT in an unselected population does not result in an accurate cTN staging as previously reported from dedicated centres. To achieve adequate preoperative cTN staging nationally, the education of radiologists and optimization of the radiological method will be necessary.